MODERN FORMS OF AUDITING AND DIRECTIONS FOR IMPROVEMENT OF INTERNAL CONTROL - B. Turabov (American Journals, 2024)
This article describes the modern forms of audit and gives brief information about the internal control system in our country. Recommendations for improving the internal control system are also mentioned.
Keywords: Accounting system, internal control system, internal standards of audit organizations, synthetic account, analytical account, importance in audit, audit risk.